The role of dominant striatum in language: a study using intraoperative electrical stimulations. Issue 7 (16th June 2005) - Robles, S Gil; Gatignol, P; Capelle, L; Mitchell, M-C; Duffau, H
Abstract : Background: The role of the striatum in language remains poorly understood. Intraoperative electrical stimulation during surgery for tumours involving the caudate nucleus or putamen in the dominant hemisphere might be illuminating. Objectives: To study the role of these structures in language, with the aim of avoiding postoperative definitive aphasia. Methods: 11 patients with cortico-subcortical low grade gliomas were operated on while awake, and striatal functional mapping was done. Intraoperative direct electrical stimulation was used while the patients carried out motor and naming tasks during the resection. Results: In five cases of glioma involving the dominant putamen, stimulations induced anarthria, while in six cases of glioma involving the dominant caudate, stimulations elicited perseveration. There was no motor effect. The striatum was systematically preserved. Postoperatively, all patients except one had transient dysphasia which resolved within three months. Conclusions: There appear to be two separate basal ganglia systems in language, one mediated by the putamen which might have a motor role, and one by the caudate which might have a role in cognitive control. These findings could have implications for surgical strategy in lesions involving the dominant striatum.